Mesenchymal stem cells: In vivo therapeutic application ameliorates carbon tetrachloride induced liver fibrosis in rats. (November 2015) - Raafat, Nermin; Abdel Aal, Sara M.; Abdo, Fadia K.; El Ghonaimy, Nabila M.
Abstract: Background: Egypt has the highest prevalence of hepatitis C virus in the world with infection rate up to 60%, for which liver fibrosis or hepatic carcinoma is the final outcome. Stem cell therapy provides a new hope for hepatic repair instead of traditional treatment, liver transplantation, as it is safer, gives long term engraftment and avoid expensive immunosuppressive drugs and unexpected hazardous effects. Aim: This work aimed at determining the therapeutic potential of mesenchymal stem cells (MSC) in hepatic repair as a new line of therapy for liver fibrosis. Methods: 33 female albino rats were divided into three groups: Group I: 10 rats injected subcutaneously with olive oil, Group II: 13 rats injected with carbon tetrachloride (CCl4) and Group III: 10 rats injected with CCl4 then bone marrow derived MSC from male rats. Blood and liver tissue samples were taken from all rats for biochemical and histological study. Results: Liver functions for group II rats showed significant deterioration in response to CCl4 in addition to significant histological changes in liver lobules and portal areas. Those parameters tend to be normal in MSC-treated group. Group III rats revealed normalized liver function and histological picture. Meanwhile, most of the pathological lesions were still detected in rats of second group. Conclusion: Undifferentiated MSCs have the ability to ameliorate CCl4 induced liver injury in albino rats in terms of liver functions and histological features. So, stem cell therapy can be considered clinically to offer a hope for patients suffering from liver fibrosis.